Giant intraoral condyloma accuminatum lesion coexisting with genital condyloma - (:unkn) unknown (PROFESSIONAL MEDICAL PUBLICATIONS, 2014)
The condyloma acuminatum (venereal wart) is a benign epithelial proliferation that occurs most frequently on the mucous membranes of the perianal and genital areas of men and women. The transmissible etiological agents of this lesion are papillomaviruses. In some rare instances these lesion can also be found in the oral cavity. In this 50-year-old woman; a wide rugose, cauliflower-like, exophytic lesion on the attached gingiva in the anterior region thought to be epulis fissuratum or a giant-cell granuloma turned out to be condyloma acuminatum following the excisional biopsy. This patient also had some genital lesions and tested positive for the human papilloma virus which is to be expected due to fact that intraoral presentation of condyloma acuminatum is a lot more frequent in patients who have anogenital lesions according to the literature. This report describes the etiology, diagnosis, treatment and follow-up an intraoral condyloma.
Keywords: Condyloma accuminatum; Oral condyloma; Genital condyloma; HPV; SEXUALLY-TRANSMITTED-DISEASES; ACUMINATUM